The Logic of masculinist protection: Reflections on the current security state - Young, Iris Marion (Signs, 2003)
Keywords: amériques; approches et analyses; discipline; discours dominant; histoire et politique; masculinité; patriarcat; philosophie; philosophie politique; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; sécurité nationale; thématiques; états-unis

Justice and the politics of difference - Young, Iris Marion; Allen, Danielle S. (Princeton University Press, 2022)
"In this classic work of feminist political thought, Iris Marion Young challenges the prevailing reduction of social justice to distributive justice. The starting point for her critique is the experience and concerns of the new social movements that were created by marginal and excluded groups, including women, African Americans, and American Indians, as well as gays and lesbians. Young argues that by assuming a homogeneous public, democratic theorists fail to consider institutional arrangements for including people not culturally identified with white European male norms. Consequently, theorists do not adequately address the problems of an inclusive participatory framework. Basing her vision of the good society on the culturally plural networks of contemporary urban life, Young makes the case that normative theory and public policy should undermine group-based oppression by affirming rather than suppressing social group differences"
Section: x, 286 pages ; 24 cm.
Keywords: 2000 à aujourd'hui; 2010-2019; amérique du nord; amériques; approches et analyses; cours; cycles supérieurs; discipline; discours dominant; fem9000; inégalités; justice sociale; phi4336; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis

Le genre, structure sérielle : penser les femmes comme un groupe social - Young, Iris Marion (Recherches féministes, 2007)
À la suite des critiques formulées par des femmes de couleur et par des lesbiennes quant à la conception ethnocentrique blanche et hétérosexiste d’une bonne partie de la réflexion féministe, l’auteure essaie de penser la catégorie « femmes » en dehors des définitions essentialisantes et totalisantes. Elle propose, à cette fin, de recourir à la notion sartrienne de structure sérielle pour penser les femmes comme un groupe social dont les membres n’ont pas nécessairement à partager les mêmes attributs. Cela lui permet d’envisager la possibilité d’un féminisme qui ne repose pas sur la catégorie « femmes » dans son ensemble, mais qui émerge plutôt des pratiques, nécessairement parcellaires, de femmes qui transforment en enjeux politiques certains aspects de la « condition féminine ». Ainsi, il devient possible de penser le féminisme comme théorie et pratique politiques sans le faire procéder de « femmes » dont la condition serait identique en tous points, mais plutôt de coalitions qui remettent en cause un aspect particulier des rapports de pouvoir entre hommes et femmes. Taking into consideration critiques from women of color or lesbians on the white ethnocentric and heterosexist character of a large part of feminist theorizing, I try to conceptualize the category “women” while avoiding both essentialism and totalisation. For this purpose, I propose to use the Sartrian concept of seriality in order to think about women as a social group, without implying that all women share a set of social attributes. This allows me to adopt a conception of feminism that does not proceed from the category “women” as a whole, but stems out of the partial practices that politicize various aspects of “women’s condition”. Thus, one can define feminism as a theory and a political practice that is not exclusive to the domain of “women”, but rather draw on various coalitions that challenge the power relation between men and women in some respect.
Number: 2 Translators: _:n14698 Première publication:1994
Keywords: 1900-1999; 1990-1999; amériques; cours; discipline; fem1000; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; théories féministes; états-unis